High population densities of Macrolophus pygmaeus on tomato plants can cause economic fruit damage: interaction with Pepino mosaic virus?. Issue 7 (17th November 2015) - Moerkens, Rob; Berckmoes, Els; Van Damme, Veerle; Ortega‐Parra, Nelia; Hanssen, Inge; Wuytack, Martine; Wittemans, Lieve; Casteels, Hans; Tirry, Luc; De Clercq, Patrick; De Vis, Raf
Abstract: BACKGROUND: The zoophytophagous predator Macrolophus pygmaeus Rambur (Hemiptera: Miridae) is a successful biocontrol agent against several pest species in protected tomato crops. This predator is considered to be harmless for the crop. However, in recent years, Heteroptera feeding punctures on tomato fruit in Belgian and Dutch greenhouses have been misinterpreted as Pepino mosaic virus (PepMV) symptoms. In this study, three hypotheses were tested: (1) M. pygmaeus causes fruit damage that increases with population density and surpasses economic thresholds; (2) the presence of prey or alternative prey reduces the damage; (3) an infection of the tomato plants by PepMV triggers or aggravates M. pygmaeus fruit damage. RESULTS: At increasing M. pygmaeus densities, the severity of fruit damage increased from a few dimples towards yellowish discoloration and deformed fruits. A correlation with an infection with PepMV was found. The severity of the symptoms was independent of the presence of prey. A minimum economic density threshold was estimated at 0.32 M. pygmaeus per leaf. CONCLUSION: M. pygmaeus can cause economic damage to tomato fruits at densities common in practice. An infection of the plants with PepMV enhances fruit symptoms significantly. Interacting plant defence responses are most likely the key to explaining this, although confirmation is required. © 2015 Society of Chemical Industry